ACCURACY OF C4.5 ALGORITHM BASED GAIN AVERAGE VALUES IN PREDICTING STUDENT VALUES - Aminuddin Indra Permana (LLDIKTI Wilayah X, 2020)
C4.5 algorithm still has weaknesses in making predictions or classifying data if the classes used in large quantities can cause increased decision-making time. Then we need an approach to improve the performance of the C4.5 algorithm in the split attribute selection process is to use the average gain value that is applied to help predict students who will become the overall champion. In research conducted on Student Value is done by producing predictions from the C4.5 method by doing the highest level of accuracy that is good. From the results of the analysis that improving the performance of the C4.5 algorithm in the split attribute selection process is to use the average gain value applied. The success in predicting using the C4.5 method using Student Grades increased by 66.3%